Polarized light - Goldstein, Dennis H. (Boca Raton, FL : CRC Press, 2011)
'An in-depth exploration of polarized light, this book covers production and uses, facilitating self-study without prior knowledge of Maxwell's equations. This third edition includes more than 2500 figures and equations along with chapters on polarization elements, anisotropic materials, Stokes polarimetry, Mueller matrix polarimetry, and the mathematics of the Mueller matrix. It features two new chapters, one on polarized light in nature and one on birefringence. It also presents a completely revised review of the history of polarized light and contains a new appendix on conventions used in polarized light'--
Includes bibliographical references and index.
Keywords: Polarization (Light); Polarization (Light) -- Industrial applications